Rhodamine 6G encapsuled mesoporous silica channels - Saran, Priscila Samara [UNESP] (2008)
We report the effect of solvent on the rhodamine 6G encapsuled into channels of mesoporous silica, synthesized by two-step process that gives intermediary stable hybrid micelles. Mesoporous materials have been obtained by the method that involves surfactant micelles (mainly cationic) and inorganic precursor of the structure to be obtained. MSU-X type mesoporous silica has been synthesized with polyethylene oxide surfactant as the directing-structure agent and tetraethyl orthosilicate Si(OEt)4 as the silica source. The influence of the solvent on the encapsulation of rhodamine dye was systematically explored, specially its influence on the luminescence properties. Rhodamine 6G encapsuled into mesoporous silica channel was characterized by UV-Vis and luminescence spectroscopies, scanning electron microscopy, small angle x ray scattering and N2 sorption-desorption. The pore size and the solvent effects into luminescence dye encapsuled into mesoporous silica channels are observed in the visible absorption and emission spectra of rhodamine 6G. The intense photoluminescence band of rhodamine 6G dye is in 500 to 600 nm region. The observed shift of the absorption and emission bands can be assigned to the effect of the solvents dielectric constant and pore size of mesoporous silica. © 2008 Trans. Tech. Publications, Switzerland.